Three Challenges in an Infant: Neuroblastoma Mimicking Infantile Hepatic Hemangioma, With Chylothorax and Rosettes in Pleural Fluid - Samin Alavi; Mitra Khalili; Maryam Kazemi Aghdam; Alireza Zamani; Tahereh Madani (Case Reports in Hematology)
Infantile hepatic hemangioma (IHH) is rare, but the most common benign hepatic tumor in the first year of life. It has a characteristic course with perinatal presentation, increasing growth during the first year of life, and subsequent shrinkage of the vascular lesions. The authors report a 12-month-old male infant who presented with severe abdominal distension and respiratory distress while under workup for diffuse IHH since 2 months of age. In addition, the child’s situation was complicated by two uncommon occurrences: bilateral chylothorax and the presence of neuroblasts and rosette cells in the pleural fluid. The detection of such cells in pleural fluid is extremely rare in pediatric neuroblastoma cases. This complex medical scenario highlights the challenges faced in diagnosing and managing rare pediatric conditions, emphasizing the need for careful monitoring and comprehensive diagnostic approaches in similar cases.